THE METHODS OF FORMATION OF THE CULTURE OF ECOLOGIC SECURITY IN STUDENTS IN THE TEACHING OF NATURAL SCIENCES - Mukhtorova Lobar Abdimannobovna (International Engineering Journal For Research & Development, 2020)
In the contemporary world the concept of environment and the formation of ecological culture among the young people is one of the most important issues in the education system of the world. This article is also dedicated to the issues of formation of environmental consciousness and culture in young people in the example of the educational system of Uzbekistan and its legal guarantees are scientifically analyzed. The article also explores ways to enhance the environmental culture of young people in school and outside the classroom.